Determinants of stress in the enterprise which improves its quality = Determinanty stresu w przedsiębiorstwie doskonalących jakość - Chojnacka, Małgorzata; Witkowski, Krzysztof (Zielona Góra: Faculty of Economics and Management Press)
Continuous development and changes in the areas of technology, organization, management and marketing may bring a number of benefits to enterprises. This can, however, also contribute significantly to employee anxiety. This article is an attempt to answer the question: What are the sources of tension and conflict, and to what degree are they being experienced? The study among employees of a quality-oriented company is intended to identify issues of stress in such organizations with particular emphasis on the determinants of this phenomenon. The paper also proposes remedial action to address such issues.
Keywords: stres; determinanty stresu; przedsiębiorstwo doskonalące jakość; stress; determinants of stress